Production and Decomposition of Litter in Plantation Forests of Eucalyptus camaldulensis Along Canal Command Area in Indian Desert - Bala, N.; Kumar, Pramod; Bohra, N. K.; Limba, N. K.; Baloch, S. R.; Singh, G. (Indian Forester, 2010)
Litter production varied greatly with plantation age and stem density in E. camaldulensis being high in 12-year-old plantation (6087 kg ha-1). Lowest litter production was in 4-year-old plantation (2042 kg ha-1). Bimodal pattern of litter fall was observed in younger plantation where, two peaks of varied intensity were observed in summer and winter. Overall, litter production was more in summer. Component wise, leaf litter accounted for the major part of the total litter production. It varied from 64% in 17-year-old plantations to 73% in 8-year-old plantations. Woody litter component varied from 16% to 23% in different age plantations. Bark litter also constitute a significant proportion of the total litter production rangingfrom 9-13%. Value of decomposition constant (k) was 0.1508, signifying very slow rate of decomposition. A significant positive relationship between annual total litter production and girth at breast height (GBH) as well as tree height was observed. Conclusively, lowrate of decomposition signified slow rate of nutrient turnover.